Complications of Endoscopic Skull Base Surgery for Sellar and Parasellar Tumors in Pediatric Population; Neurosurgical Perspectives - Yang, Jeyul; Kim, Yong Hwy; Phi, Ji Hoon; Kim, Seung-Ki; Wang, Kyu-Chang (Frontiers in Oncology, 2022)
Background: Advances in surgical techniques based on in-depth anatomical knowledge of the skull base have broadened the indications for endoscopic skull base surgery (ESS) with the advantage of wide and direct surgical exposure while minimizing invasiveness. However, the low incidence of the indicated diseases and narrow surgical corridors in children have limited the popularization of ESS. In addition, surgical complications and preventive interventions are not yet well known. Therefore, we retrospectively investigated the complications and prevention methods of ESS in children with a comprehensive review. Methods: We retrospectively analyzed the medical records of pediatric patients who underwent ESS for sellar and parasellar tumors at Seoul National University Children’s Hospital from July 2010 to December 2020. Visual and endocrine status, extent of resection, complications, and recurrences were investigated depending on the pathology of the tumor. In addition, a comprehensive literature review regarding the complications of pediatric ESS was performed. Results: A total of 98 patients were enrolled. The median age of the patients was 12 years, and 52 patients were male. Preoperative visual disturbance was found in 53 patients, anterior pituitary function deficit in 69, and diabetes insipidus in 32. Gross total resection was attempted in 67 patients and achieved in 62 (93%). Biopsy and cyst fenestration were the goals of surgery in 26 patients, and all were achieved as planned. Regarding outcomes, visual disturbance worsened in two patients (2%), endocrine status was aggravated in 34 (35%) patients, and new-onset diabetes insipidus occurred in 27 (41%) patients. The overall surgical complication rate (other than aggravation of visual or endocrine status) was 17%. Postoperative infection (12%) was the most common complication, followed by cerebrospinal fluid leakage (2%), vasospasm, hemorrhage and infarction. By pathological diagnosis, craniopharyngioma had the highest complication rate of 29%. All but one patient with postoperative hemorrhage showed no permanent deficits. Conclusion: ESS in children is feasible and relatively safe. More attention and different postoperative management protocols are required in children to avoid complications, especially in craniopharyngiomas. However, the complications can be mostly managed conservatively without permanent neurologic deficits.